Physical activity is related to disease severity and fatigue, but not to relapse rate in persons with relapsing remitting multiple sclerosis – a self-reported questionnaire based study - Schlagheck, Marit L.; Hübner, Sven T.; Joisten, Niklas; Walzik, David; Rademacher, Annette; Wolf, Florian; Bansi, Jens; Warnke, Clemens; Zimmer, Philipp (Frontiers in Neurology, 2023)
Introduction Based on theoretical models, physical activity has been introduced as a promoting method to mitigate the disease severity, fatigue and relapse rate in multiple sclerosis. The primary objective of the study was to investigate the relation between self-reported physical activity level and disease severity, fatigue and relapse rate in persons with relapsing remitting multiple sclerosis (RRMS). Methods A survey was offered to persons with RRMS from March 2019 to August 2021 (n = 253). Physical activity level, fatigue and disease severity were determined using the Godin Leisure-Time Questionnaire (GLTEQ), the Patient Determined Disease Steps (PDDS) scale and the Fatigue Scale for Motor and Cognitive Functions (FSMC). Additionally, participants’ relapse rate was recorded. Results Bivariate correlations revealed an inverse relation between physical activity level and PDDS (ρ = −0.279; p < 0.001) as well as between physical activity and FSMC (r = −0.213, p < 0.001), but not between physical activity and relapse rate (r = 0.033, p > 0.05). Multiple linear regression analyses explained 12.6% and 5.2% of the variance of PDDS and FSMC. Conclusion Our findings confirm a relation between self-reported physical activity, disease severity and fatigue in persons with RRMS. However, self-reported physical activity level does not seem to affect the annualised relapse rate.